Exploring our world - Boehm, Richard G.; Armstrong, David G.; Hunkins, Francis P. (McGraw-Hill/Glencoe, 2010)
Unit 1. The world -- Unit 2. Europe -- Unit 3. Russia -- Unit 4. North Africa, Southwest Asia, and Central Asia -- Unit 5. Africa south of the Sahara -- Unit 6. South Asia -- Unit 7. East Asia and Southeast Asia -- Unit 8. Australia, Oceania, and Antarctica.